Analisis Faktor-Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Dana Desa Tahun 2019 (Studi Empiris Pada Desa se-Kecamatan Pecangaan Kabupaten Jepara) - Ennida Novanti; Fatchur Rohman (Jurnal Rekognisi Akuntansi, 2021)
In managing village funds, an aspect of good governance is required where one of the pillars is accountability. Accountability is an obligation to provide accountability to the trustee. Indicators of accountability for village fund management are the competence of village fund management officers (X1), village government organizational commitment (X2) and the use of information technology (X3). This study uses primary data in the form of data obtained directly from the field, the population in this study is all village officials in Pecangaan District. While the sample of this study amounted to 60 people consisting of senior officials, village secretaries, heads of financial affairs, heads of planning affairs and heads of welfare sections. The data analysis method used in this study is multiple regression analysis using SPSS for Windows version 26 software. While the Village Government Organizational Commitment has no significant positive effect (no effect) on Village Fund Management Accountability.